Marketing of Conybio Products - A Study with Reference to Rajapalayam Taluk - Kanthakrishnan, R.; Malaikani (Indian Journal of Marketing, 2007)
Conybio Healthcare (India) Private Limited is engaged in Multi Level Marketing business. It started its operation in Malaysia in 1995, and is currently established in nine countries. Conybio is at present operating in Singapore, Thailand, Indonesia, Brunei, Philippines, Hon Kong and Canada. India is the ninth country and the company has its base at Chennai. It started its activities in India in 1998. Conybio India commenced its operations with just 12 FIR (Far Infrared Ray) Bioceramic products and now it has over 45 products. It provides dual benefits of good health and a lot of wealth leading to ultimate happiness.Conybio has already made in roads into the South, East and West Indian markets and now is all set to storm the North Indian market. One of the many reasons for the fast expansion in India is, the uniqueness of FIR products. They are effective and have caught the imagination of the Indian people, with regard to its efficacy along with "one of kind" simple accumulative marketing plan.